Associations between quality of work features in primary health care and glycaemic control in people with Type 2 diabetes mellitus: A nationwide survey - Husdal, Rebecka (A pilot randomized controlled trial examining the feasibility, acceptability, and efficacy of Adapted Motivational Interviewing for post-operative bariatric surgery patients, 2019)
• Real life clinical data are needed to understand benefits of quality of work (QOW). • Examines associations between primary health care centres’ QOW and HbA1c levels. • An explorative factor analysis identified seven QOW features. • QOW involving an individualized treatment plan decreased HbA1c level in all groups. • More effective QOW strategies are needed to support people with uncontrolled HbA1c.